Математические модели случайных объектов в телекоммуникациях - Поповский, В. В. (Проблеми телекомунікацій, 2010)
In the given article analyzed two basic kinds of the stochastic models are analyzed. These models are used for solving problems in telecommunications. These are the models, based on probabilities of parameters of casual objects and model of these objects, describing conditions. It is confirmed, that the second approach is more exact, adequate and constructive, by virtue of a greater generality.
Keywords: случайный объект в телекоммуникациях; телекоммуникации